AB0243 Relationship between bone mineral density and radiographic damage in established rheumatoid arthritis patients under biologics. (23rd January 2014) - Bernardes, M.; Vieira, T.; Terroso, G.; Abelha-Aleixo, J.; Madureira, P.; Vieira, R.; Fonseca, R.; Gonçalves, D.; Bernardo, A.; Pimenta, S.; Oliveira, A.; Faria, T.; et al.
Abstract : Background: Rheumatoid arthritis (RA) is characterized by a periarticular demineralization, namely in the hands, as well as a generalized osteoporosis. Both processes and joint damage are related to an imbalance in osteoclast and osteoblast activity. Objectives: To determine the relation between bone density and metabolism with radiographic damage in patients with established rheumatoid arthritis (RA) under biologics. Methods: Clinical features and peripheral blood samples were collected. The Portuguese version of HAQ, the disease activity score (DAS28 (4v)), the number of painful (out of 68) and swollen (out of 66) joints were obtained. We measured the following laboratory parameters: ESR and CRP, serum β-C-telopeptides of type 1 collagen cross-links (β-CTX1), osteocalcin, Dkk-1 (ELISA, Biomedica), sclerostin (ELISA TECOmedical), RANKL (ELISA, Cusabio) and OPG (ELISA, Biomedica). Bone mineral density (BMD) was assessed by Dual energy X-ray Absorptiometry (Lunar Expert ® 1320) at the lumbar spine, total hip, femoral neck, Wards triangle, hands and second proximal phalanges. Hands and feet X-ray examinations were scored according to the Sharp van der Heijde score (SHS) by a single reader. Spearman correlations were used for statistical analysis (PASW Statistics 18). Results: We evaluated 104 RA patients, 88 (84, 6%) women, age 52.4 ± 11.50 years, disease duration 16.7 ± 8.94 years, mean DAS28 (4v) of 4.31 ± 1.277 and a mean HAQ of 1.29 ± 0.614. In our sample, 85 (81, 7%) were under anti-TNFalpha agents, 27 (26%) under bisphosphonates and 43 (41, 3%) under vitamin D supplements. Total SHS and erosion score were negatively correlated with BMD at the hip (r=-0.321; p<0.005 vs r=-0.326; p<0.05), femoral neck (r=-0.270; p<0.05 vs r=-0.282; p<0.01), Wards triangle (r=-0, 333; p<0, 005 vs r=-0, 321; p<0, 005), lumbar spine (r=-0.261; p<0.05 vs r=-0.263; p<0.05), right hand (r=-0.401; p<0.001 vs r=-0.417; p<0.001), left hand (r=-0.449; p<0.001 vs r=-0.456; p<0.001), right second proximal phalange (r=-0.276; p<0.05 vs r=-0.261; p<0.05) and left second proximal phalange (r=-0.396; p<0.001 vs r=-0.384; p=0.001). In terms of bone markers, only RANKL levels were weakly correlated with the erosion score (r=-0.218; p<0.05). Conclusions: In our rheumatoid arthritis population under biologics, the radiographic damage evaluated by SHS was better correlated with femoral and hands BMD than with lumbar spine BMD. RANKL seems to be the only bone marker of interest in order to define the most erosive subgroup of patients. Disclosure of Interest: None Declared